Students’ Perception on the Use of Webtoon in Reading Activity - Utama, Estu Yoga Cahya (RETAIN : Journal of Research in English Language Teaching, 2025)
This study aims to find out students’ perception on the role of the Webtoon in their reading activity. This current study takes place in a 10th-grade class in senior high school. This study uses qualitative research, especially case study. The data analyzed by giving open-ended questionnaire and interviewing some 10th-grade students in the class. The results of the questionnaire and interviews showed that students using Webtoon in their meantime, also they learn something and shows positive responses about the use of Webtoon in their reading activity. Based on the findings, it can be concluded that students’ perception on the use of Webtoon in their reading activity shows positive results. Students can study in the meantime by reading Webtoon and they can study outside of the school.